Identitas City Branding, Analisis Tampilan Identitas Daerah pada Cover Infografis Bekraf RI - Wiradharma, Gunawan; Arisanty, Melisa; Riady, Yasir; Anam, Khaerul; Prasetyo, Mario Aditya (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
The Creative Economic Agency of the Republic of Indonesia (Bekraf RI) has produced 57 infographics throughout 2016-2018 from Independent Assessment of Creative City/ District for Indonesia (PMK3I). One of the exciting parts of those infographics is the cover related to city branding's identity in developing the creative economy in an area. This study aims to determine what identities are displayed in city branding. This research used the theory of city image management by Kavaratzis. The methodology used is descriptive qualitative with content analysis techniques. The research data used are infographics cover of Creative Economic Agency of the Republic of Indonesia in Malang, Yogyakarta, and Jakarta. The data collection technique was carried out by in-depth interviews with informants who worked in the tourism sector government agencies and were native to those areas. In representing cities/regions in Indonesia, physical buildings, cultural products, and community characters are always connected to their local identity.